Educação emocional e espiritualidade na promoção de saúde: um estudo sobre a participação dos colaboradores do NUCOM-IESP em práticas de alongamento, massagem e meditação - Cavalcanti, Jeane Odete Freire dos Santos (2019)
The present work proposes to make an analysis on the relevance of Emotional Education and spirituality for health promotion of the employees of Núcleo de Comunicação e Marketing - NUCOM from Instituto de Educação Superior da Paraíba - IESP. In this sense, we have observed the possibilities of multi-perspectives of faith in overcoming the incurable diseases, since spirituality has presented itself as something that exists and it is placed as a direct partner of health. From Thorwald Dethlefsen and Rüdiger Dalke (2007)' approach, which shows that patients as the author of its own diseases, several authors were also sought, such as Ferdinand Rörh (2012) and Fabricio Possebon (2016; 2017) which mentions the Constitution of Self, the Comprehensiveness of Self and a Harmony which results in Health; Koeing (2012), which addresses issues of health and spirituality; Adam and Herzlich (2001), both working on the sociology of disease and medicine exposing the concepts of disease and cure; Elisa Possebon (2017; 2015), presenting Emotional Education; (1990), Damasio (1996, 2000), Maturana (2000), Mkolajaczak and Desseilles (2012), and Malta (2016), among others, who are the basis for the PNPS and PIC studies, also in particular, Clemenceau, Dalavier and Gundill (2012); Lidell (2002), Golemam (1999), Vaisberg and Mello (2010), writing mainly about stretching, meditation and massage. Other theorists were added to this study such as Filoramo and Prandi (2012); Klaus Hock (2010); Emerson Silveira (2016); Marcelo Camurça (2008) discussing the Sciences of Religions and their methodological polytheism, thus constructing a theoretical framework that supports the choice of this discussion under the lights of this dynamic and plural science. The research is justified as a qualitative nature, with a methodology based on a phenomenological approach, since it does not dissociate emotions and spirituality and multi perspectives from coping with chronic diseases and seeking health. This situation is associated with the needs of understanding how the anguish of the spirit influences the quality of life of the people, even when they are sentenced to a commitment to the right for a healthy life, through confirmed diagnoses of chronic diseases. As a Field of Research, we use the Extension Program in Stretching, Massage and Meditation of IESP, which counts with the participation of the employees at NUCOM. To make our data, we used instruments like Mandala Art Therapy to diagnose the emotional characteristics of the individuals involved and the application of a questionnaire to identify the individual characteristics, work identification and health-related issues. The results display the participants of this research - the collaborators of the NUCOM; classified as having a good quality of life, but the fields that comprise physical, psychological aspects, personal relationships and environment are regular, as well as satisfaction with their health in general. Some relevant benefits are pointed out regarding to the development of emotional education from the applied techniques of stretching, massage and meditation, including the Mandala Art Therapy as a wish from the participants. It was also pointed out the need for a greater interaction in the way the participants were mobilized for effective participation toward the practices, requiring scheduling adjustments. Finally, it was proposed the strengthening of the studies on the topic discussed here together with those responsible for the projects that aim at improving the quality of life of IESP employees, according to the knowledge of the results produced.